1993
DOI: 10.1038/364626a0
|View full text |Cite
|
Sign up to set email alerts
|

A redox-based mechanism for the neuroprotective and neurodestructive effects of nitric oxide and related nitroso-compounds

Abstract: Congeners of nitrogen monoxide (NO) are neuroprotective and neurodestructive. To address this apparent paradox, we considered the effects on neurons of compounds characterized by alternative redox states of NO: nitric oxide (NO.) and nitrosonium ion (NO+). Nitric oxide, generated from NO. donors or synthesized endogenously after NMDA (N-methyl-D-aspartate) receptor activation, can lead to neurotoxicity. Here, we report that NO.- mediated neurotoxicity is engendered, at least in part, by reaction with superoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

35
1,325
3
26

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,368 publications
(1,389 citation statements)
references
References 30 publications
35
1,325
3
26
Order By: Relevance
“…First, studies have suggested that changes in ambient redox milieu may switch the influence of NO from neurotoxicity to neuroprotection. 15 Secondly, the role of NO seems to depend on the time of NO release and the cellular location of the NOgenerating enzyme. Whereas previous studies on knockout mice in our laboratory indicate an involvement of nNOS in secondary damage after SCI, 16 less is known about the influence of eNOS.…”
Section: Discussionmentioning
confidence: 99%
“…First, studies have suggested that changes in ambient redox milieu may switch the influence of NO from neurotoxicity to neuroprotection. 15 Secondly, the role of NO seems to depend on the time of NO release and the cellular location of the NOgenerating enzyme. Whereas previous studies on knockout mice in our laboratory indicate an involvement of nNOS in secondary damage after SCI, 16 less is known about the influence of eNOS.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 The mechanisms of extracellular EAA accumulation after SCI may include both increasing release from vesicles, injured cells or blood and decreasing uptake by astrocytes and neurons. 41,43 Intrathecal administration of NMDA, at a dose with no e ects on uninjured animals, signi®cantly worsens recovery after SCI. 21 On the basis of these ®ndings, several investigators analyzed NMDA receptor antagonists for the treatment of experimental SCI or ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Besides a role in differentiation and synaptic plasticity, NO • has also been implicated in neuronal apoptosis, and consequently, in neurodegenerative diseases, specifically when NO • production is increased to toxic levels [49,64,77,123,202]. In particular, NO • has been linked to the phenomenon of excitotoxicity involving the over-stimulation of the NMDA receptor by glutamate, subsequently triggering a strong intracellular accumulation of Ca 2+ [141].…”
Section: Nitric Oxide and Mapk Signalingmentioning
confidence: 99%